Rethinking on Using of Traditional Indigenous Medicinal Plants for the Management of Covid-19 In India- A Review (International Journal of Ayurveda and Pharma Research, 2021)
Novel corona virus first began in Wuhan, china, in December 2019, and it rapidly expanded globally. Corona virus disease 2019 (COVID-19) is a new infectious disease caused by severe acute respiratory syndrome corona virus 2 (SARS-CoV-2) that belongs to the corona virus family. With no specific and effective antiviral therapy for CoVID-19, new or repurposed antiviral are urgently needed. For traditional medicinal treasure India is well recognized all over the world. There are more than 3000 authorized plants in India that hold prodigious medicinal potential. The traditional systems of medicines viz. Ayurveda, Siddha, Unani, western herbal medicine, traditional Chinese medicine and homeopathy have roots in medicinal herbs. In view of the significant morbidity and mortality associated with this pandemic, many research activities are ongoing globally to explore possible therapeutic regiments or prophylactic agents. Ayurveda the traditional system of Indian medicine can offer prophylactic or therapeutic solutions for COVID-19. Traditional Indian Medicines has lot to offer in the management of COVID-19. Many research documents suggested that ethno pharmacological information on the medicinal plant species used by herbalists against corona virus disease. Herbal medicine are achieving attention because of the extensive therapeutics like potent antiviral, immunomodulatory, anti-inflammatory, and anti-oxidant properties and certain natural compounds might be effective for the treatment of COVID-19 based on general concepts from previous experiments. These articles discusses some herbal agents extracted from various plants, including Cinchona, Curcuma longa, Nigella sativa, Azadirachta indica, Tinospora Cordifolia, Allium sativum, Oxylum indicum, Punicagranatum, Cocos nucifera and some more plants, Herbal medicine, phytochemical which are considered for the treatment of COVID-19. This review will open an area for the development of novel natural herbal formulations as an alternative therapy that can be used for the preparation of immunopotentiator, development of herbal/Ayurvedic antiviral drugs, designing anti-microbial / anti viral materials and prevention and treatment of COVID-19.